The effect of the Lokomat® robotic-orthosis system on lower extremity rehabilitation in patients with stroke: a systematic review and meta-analysis - Wu, Lina; Xu, Gui; Wu, Qiaofeng (Frontiers in Neurology, 2023)
Background The Lokomat® is a device utilized for gait training in post-stroke patients. Through a systematic review, the objective was to determine whether robot-assisted gait training with the Lokomat® is more effective in enhancing lower extremity rehabilitation in patients with stroke in comparison to conventional physical therapy (CPT). Methods In this study, a systematic search was conducted in various databases, including CINAHL, MEDLINE, PubMed, Embase, Cochrane Library, Scopus, Web of Science, and Physiotherapy Evidence Database (PEDro), as well as bibliographies of previous meta-analyses, to identify all randomized controlled trials that investigated the use of Lokomat® devices in adult stroke patients. The study aimed to derive pooled estimates of standardized mean differences for six outcomes, namely, Fugl–Meyer Assessment lower-extremity subscale (FMA-LE), Berg Balance Scale (BBS), gait speed, functional ambulation category scale (FAC), timed up and go (TUG), and functional independence measure (FIM), through random effects meta-analyses. Results The review analyzed 21 studies with a total of 709 participants and found that the use of Lokomat® in stroke patients resulted in favorable outcomes for the recovery of balance as measured by the BBS (mean difference = 2.71, 95% CI 1.39 to 4.03; p < 0.0001). However, the FAC showed that Lokomat® was less effective than the CPT group (mean difference = −0.28, 95% CI −0.45 to 0.11, P = 0.001). There were no significant differences in FMA-LE (mean difference = 1.27, 95% CI −0.88 to 3.42, P = 0.25), gait speed (mean difference = 0.02, 95% CI −0.03 to 0.07, P = 0.44), TUG (mean difference = −0.12, 95% CI −0.71 to 0.46, P = 0.68), or FIM (mean difference = 2.12, 95% CI −2.92 to 7.16, P = 0.41) between the Lokomat® and CPT groups for stroke patients. Conclusion Our results indicate that, with the exception of more notable improvements in balance, robot-assisted gait training utilizing the Lokomat® was not superior to CPT based on the current literature. Considering its ability to reduce therapists' work intensity and burden, the way in which Lokomat® is applied should be strengthened, or future randomized controlled trial studies should use more sensitive assessment criteria.